Safety assessment of the process 'Märkische Faser', based on NGR technology, used to recycle post‐consumer PET into food contact materials. (14th July 2017) - ; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; Kärenlampi, Sirpa; et al.
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety assessment of the recycling process Märkische Faser (EU register number RECYC0135), which is based on the Next Generation Group (NGR) technology. The input to this process is hot washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, containing no more than 5% PET from non‐food consumer applications. In this technology, post‐consumer washed and dried PET flakes are melted and degassed in an extruder under vacuum (step 2) and decontaminated during a melt‐state polycondensation under high temperature and vacuum (step 3). In step 4, the melt material is homogenised, extruded under vacuum and subsequently pelletised. Having examined the results of the challenge test provided, the Panel concluded that the steps 2, 3 and 4, are the critical steps for the decontamination efficiency of the process. The operating parameters which control the performance of these steps are well defined and are the temperature and pressure in all steps and the exposed surface area of the melt and its residence time of step 3. It was demonstrated that the recycling process under evaluation is able to ensure that the level of migration of potential unknown contaminants into food is below a conservatively modelled migration of 0.1 μg/kg food. The Panel concluded that recycled PET obtained from the process Märkische Faser is not of safety concern when used up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature. Thermoforming trays are not intended to be used and should not be used in microwave and conventional ovens.